Atmospheric pressure plasma assisted immobilization of hyaluronic acid on tissue engineering PLA-based scaffolds and its effect on primary human macrophages; Materials and Design; Vol. 127 - Kudryavtseva V. L. Valeriya Lvovna; Stankevich K. S. Ksenia Sergeevna; Gudima A. Aleksandru; Kibler E. V. Elina Vitaljevna; Zhukov Yu. N. Yury Nikolaevich; Bolbasov E. N. Evgeny Nikolaevich; Malashicheva A. B. Anna Borisovna; Zhuravlev M. V. Mikhail Valerievich; Ryabov V. B. Vladimir Borisovich; Liu T. Tengfei; Filimonov V. D. Viktor Dmitrievich; Remnev (Remnyov) G. E. Gennady Efimovich; et al. (2017, 2017)
Title screen